Aspects of the assessment and management of pharyngoesophageal dysphagia. Issue 1 (13th August 2020) - Allen, Jacqueline; Dewan, Karuna; Herbert, Hayley; Randall, Derrick R.; Starmer, Heather; Stein, Ellen
Abstract: Swallowing complaints are common and may have significant consequences for nutrition and pulmonary health. Etiology varies and different aspects of the deglutitive system may be affected. A thorough assessment from the oral cavity to the stomach will provide physiologic information that enables specific targeted management plans to be devised. Although the swallow trajectory bridges anatomic areas, there has previously been a tendency to compartmentalize assessment and treatment by arbitrary anatomic boundaries. It is now clear that this approach fails to appreciate the complexity of swallow mechanics and that systems (oral, pharyngeal, esophageal, and pulmonary) are intertwined and codependent. Swallowing specialists from different backgrounds and with complementary skill sets form a multidisciplinary team that can provide insight and address multiple areas of management. With the advent of new tools for instrumental evaluation, such as manometry, targeted rehabilitative strategies can be informed by physiology, increased in precision and breadth, and assessed quantitatively. Surgical approaches have evolved toward endoscopic techniques, and food technology is expanding options in dietary management. The multidisciplinary team is core to managing this varied and often neglected patient population. This review is for clinicians treating swallowing disorders and will explore the selected aspects of the assessment and management of pharyngoesophageal swallowing disorders. Abstract : Swallowing complaints are common and may have significant consequences for nutrition and pulmonary health. Swallowing specialists from different backgrounds and with complementary skill sets form a multidisciplinary team that can provide insight and address multiple areas of management. This review is for clinicians treating swallowing disorders and will explore the selected aspects of the assessment and management of pharyngoesophageal swallowing disorders.